Strategi Pengembangan Komoditas Unggulan Perikanan Budidaya di Kabupaten Magelang - Octoriani, Widyanti; Junia Sara, Rafika Sandia; Zalianti, Rosita; Amalina, Putri (Jurnal Akuakultur Sungai dan Danau, 2026)
The fisheries sector in Magelang Regency, Central Java Province, is one of the regencies/cities with considerable potential, particularly in the aquaculture sector. The objective of this study is to analyze the main flagship commodities of aquaculture in Magelang Regency and to formulate development strategies. This study was conducted in Magelang Regency, Central Java Province, in June 2024 using a descriptive method. The data used consisted of primary and secondary data. The secondary data utilized were time-series data spanning the period from 2019 to 2022. The primary data were obtained from interviews with 30 aquaculture farmers in Magelang Regency. The analytical methods used in this study were the Location Quotient (LQ) and the Specialization Index (SI). The types of fish commodities farmed in Magelang Regency include freshwater pomfret, catfish, gurami, carp, tilapia, and tawes. The carp commodity produced the highest LQ value and dominated among similar commodities at 4.07%. Consequently, there is a specialization in aquaculture production in Magelang Regency, specifically in carp and tilapia. The commodity with the highest SI value is tilapia, with an SI value of 1389%. Various strategies for developing flagship aquaculture commodities can be implemented across various aspects, such as pre-production, production, and marketing